Development and application of a Puccinia triticina avirulence gene AvrLr15-specific molecular marker - Jin, Yuqing; Cui, Zhongchi; Song, Maoxing; Yuan, Shitao; Ding, Dashuo; Liu, Yuanxia; Yin, Shuxin; Xu, Peiyuan; Yan, Chengyi; Liu, Daqun; Wu, Zhihui; Wang, Haiyan (Frontiers in Plant Science, 2025)
Puccinia triticina (Pt) races vary frequently, and new virulence races continue to emerge, leading to a lack of durable resistance in wheat cultivars. Therefore, monitoring avirulence gene composition and variation in Pt is crucial. In our previous study, we identified an avirulence protein AvrLr15 from Pt that induced Lr15-dependent immune responses and found that evasion of Lr15-mediated resistance in wheat was associated with a deletion and point mutations of amino acids in AvrLr15. In this study, TcLr15–Thatcher hybrid materials and Lr15 mutant materials were developed, which further confirmed the reliability of AvrLr15. A duplex PCR assay using two primer pairs (M1-F/M1-R and M2-F/M2-R) designed based on the differences between AvrLr15 and virulence gene avrLr15 successfully differentiated avirulent and virulent races, which can be used as the AvrLr15 marker. A total of 21 races with different virulence to Lr15 were tested to confirm the reliability of the AvrLr15 molecular marker. A total of 168 Pt isolates were collected from 15 provinces in 2024, and the AvrLr15 molecular marker can monitor the distribution of the V15 (virulent to the Lr15 gene) race and assess the durability of Lr15-mediated resistance effectively. Our findings developed the first Pt avirulence gene molecular marker to monitor natural Pt populations and guide the deployment of Lr15-resistant wheat cultivars in the field.